Markov Chain Method to Predict The Sustainability of E-Money Use by Young People in Yogyakarta - Najwa, Shofiatun; Haerunisa, Ia; Nabila, Asyifa Eka; Khaitsa, Qina (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2024)
The rapid development of digital technology has significantly driven the widespread adoption of electronic money (e-money), particularly among young adults who are generally more adaptive to technological innovations in payment systems. This study aims to predict the sustainability of e-money usage using a Markov chain model approach. Primary data was obtained through a survey of 100 respondents aged 17-30 years, who described their preferences for three e-money services: Dana, Mobile Banking, and ShopeePay. The analysis results show that Mobile Banking has the highest retention rate (62%) and is likely to be the dominant service in the long run. The steady-state prediction indicates that 57.48% of users will continue to use Mobile Banking, while Dana and ShopeePay decline to 19.01% and 23.51% respectively. Although e-money usage is still high, there is a tendency for preference shifts as well as a potential decline in sustainability. Therefore, digital service providers need to respond to this dynamic with innovative strategies to maintain the engagement of young users. This research contributes both theoretically through the application of mathematical models in digital consumer behaviour, and practically for the development of technology-based financial business strategies.